PENGARUH LITERASI KEUANGAN, GAYA HIDUP DAN PENGGUNAAN E-MONEY TERHADAP PERILAKU KONSUMTIF DI KALANGAN GENERASI Z - Cindy Mahardika Feren; Maria Agatha Sri W H; Moh Gufron (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Rapid advancements in digital technology and cashless payment systems have contributed to increasing consumptive behavior among Generation Z. This study aims to analyze the effect of financial literacy, lifestyle, and e-money usage on the consumptive behavior of Generation Z in Tulungagung Regency. This associative quantitative study involved 200 Generation Z respondents aged 18–24 selected through purposive sampling techniques. Data were collected via structured questionnaires and analyzed using multiple linear regression via SPSS 27 software. The findings reveal that financial literacy (β=0.236; p=0.000), lifestyle (β=0.745; p=0.000), and e-money usage (β=0.112; p=0.000) have positive and significant partial effects on consumptive behavior. Lifestyle emerged as the most dominant variable based on the largest standardized Beta coefficient. Simultaneously, all three independent variables significantly influenced consumptive behavior (F=1069.215; p=0.000), explaining 94.2% of the variance (